Prediction of clinical outcome using blood flow volume in the superior mesenteric artery in patients with pseudomyxoma peritonei treated by cytoreductive surgery. Issue 10 (October 2017) - Dohan, A.; Barral, M.; Eveno, C.; Lo Dico, R.; Kaci, R.; Pasteur-Rousseau, A.; Soyer, P.; Pocard, M.; Bonnin, P.
Abstract: Background: Pseudomyxoma peritonei (PMP) is a rare carcinomatosis limited to the peritoneal cavity, mainly supplied by the superior mesenteric artery (SMA). The only curative treatment is cytoreductive surgery (CRS) associated with hyperthermic intraperitoneal chemotherapy. This study aimed to evaluate the ability of blood flow volume (BFV) recorded in the SMA using Doppler ultrasonography pre-operatively to predict the extent and resectability of the disease and post-operatively to assess clinical outcome. Methods: BFV was measured in the SMA of forty-nine patients before and the year following CRS. Patients were categorized in 3 groups according to clinical and surgical outcomes: group-1 (n = 22): patient with completed CRS, group-2 (n = 16): incomplete resection with slowly progressive disease (alive at 2 years without severe clinical symptoms), group-3 (n = 11): incomplete resection and with severe clinical symptoms or dead within two years. Results: Pre-operative mean SMA BFV was higher in group-2 (510 mL/min, p  = 0.027) and in group-3 (572 mL/min, p  = 0.004) than in group-1 (378 mL/min). After surgery, BFV dropped to normal values (203 mL/min, p  = 0.001) in group-1, and to 423 mL/min ( p  = 0.047) in group-2. It remained elevated in group-3 (626 mL/min, p  = 0.566). BFV allowed stratification of 1) resectability before CRS (group-2 and -3 vs group-1, area under the ROC curve: 0.794 [0.650–0.939]), and 2) non progression after incomplete CRS (group-3 vs group-2, area under the ROC curve: 0.827 [0.565–1.00]. Conclusions: Pre-operative BFV in the SMA correlates with extent and resectability of PMP. After incomplete surgery, post-operative BFV might aid in identifying patients who may benefit of post-operative therapy.